Awakening of interlligence . - Krishnmurti. J. (London, 1973)
This comprehensive record of J K s teachings is an excellent wide ranging introduction to the insights of the great philosopher and religious teacher. Apart from existential issues such as violence, insecurity, conflict, fear and suffering , JK examines larger but related questions such as the role of the guru, the traditional methods prescribed by Vedanta and the relationship between thought and intelligence.
Keywords: Learning .